Ambivalences of Technological Literacy and Cognitive Growth: A Learning Classroom Dynamic in the Disruptive Era - Hertiki, Hertiki; Nurbani, Armelia Nungki; Setiawan, Rahmat; Agustina, Eliasanti; Mayangsari, Sekar (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This research aims to reveal the ambivalence of using technology in the learning process. The research methodology employed is qualitative. The research approach employed in this study is a case study. The data utilised in this study comprises statements extracted from a Forum Group Discussion (FGD). The data source consists of the FGD transcripts. Two ELT lecturers, one concentrates in English Writing and another in Translation, were put in sharing ideas session during the Focus Group Discussion (FGD). The data collection technique employed in this research is focus group deliberations. The data gathering method utilised in this study is the Single Focus Group (FGD). The analytical approach employed in this work is thematic analysis. From the FGDs conducted, two axes of answers were found. The first is related to how the utilisation of technology, such as AI (Artificial Intelligence), is a must. There are two points related to the necessity of technology integration in learning: 1) Improving Access and Learning Opportunities and 2) Increasing Student Motivation and Engagement. The second, on the other hand, the utilisation of technology in the learning process also reflects a very ironic phenomenon. There are two main reasons why the utilisation of technology in learning is very dilemmatic at the moment: 1) Balanced Potential Benefits and Risks, and 2) Educational Paradigm Shift. The details of these findings can be traced from the elaboration of key points from the excerpts of discussions with lecturers when sharing teaching experiences in this disruptive era.